An Evaluation of Mobile Health Application Tools - Sama, Preethi R; Eapen, Zubin J; Weinfurt, Kevin P; Shah, Bimal R; Schulman, Kevin A (JMIR Publications, 2014)
BackgroundThe rapid growth in the number of mobile health applications could have profound significance in the prevention of disease or in the treatment of patients with chronic disease such as diabetes. ObjectiveThe objective of this study was to describe the characteristics of the most common mobile health care applications available in the Apple iTunes marketplace. MethodsWe undertook a descriptive analysis of a sample of applications in the "health and wellness" category of the Apple iTunes Store. We characterized each application in terms of its health factor and primary method of user engagement. The main outcome measures of the analysis were price, health factors, and methods of user engagement. ResultsAmong the 400 applications that met the inclusion criteria, the mean price of the most frequently downloaded paid applications was US $2.24 (SD $1.30), and the mean price of the most currently available paid applications was US $2.27 (SD $1.60). Fitness/training applications were the most popular (43.5%, 174/400). The next two most common categories were health resource (15.0%, 60/400) and diet/caloric intake (14.3%, 57/400). Applications in the health resource category constituted 5.5% (22/400) of the applications reviewed. Self-monitoring was the most common primary user engagement method (74.8%, 299/400). A total of 20.8% (83/400) of the applications used two or more user engagement approaches, with self-monitoring and progress tracking being the most frequent. ConclusionsMost of the popular mobile health applications focus on fitness and self-monitoring. The approaches to user engagement utilized by these applications are limited and present an opportunity to improve the effectiveness of the technology.